Is Absolute Pitch Associated With Musical Tension Processing? - Jiang*, Jun (Iperception, 2020)
Absolute pitch (AP) is a superior ability to identify or produce musical tones without a reference tone. Although a few studies have investigated the relationship between AP and high-level music processing such as tonality and syntactic processing, very little is known about whether AP is related to musical tension processing. To address this issue, 20 AP possessors and 20 matched non-AP possessors listened to major and minor melodies and rated the levels of perceived and felt musical tension using a continuous response digital interface dial. Results indicated that the major melodies were perceived and felt as less tense than the minor ones by AP and non-AP possessors. However, there was weak evidence for no differences between AP and non-AP possessors in the perception and experience of musical tension, suggesting that AP may be independent of the processing of musical tension. The implications of these ﬁndings are discussed.